STABILITY OF CLINOHUMITE IN THE SYSTEM MGO-SIO2-H2O - Pawley A. (My University, 2000)
The low-pressure stability of clinohumite has been investigated in phase-equilibrium experiments on the reaction forsterite + brucite = clinohumite. The reaction was bracketed between 2.45 and 2.84 GPa at 650 °C, extending to between 1.37 and 1.57 GPa at 850 °C. At temperatures above the reaction brucite = periclase + vapour, the reaction clinohumite = forsterite + vapour was bracketed between 1.27 and 1.52 GPa at 900 °C, rising to between 1.90 and 2.00 GPa at 1000 °C. The position of the reaction forsterite + brucite = clinohumite is ~0.5 GPa below the position determined in previous work, the difference arising either from pressure uncertainties in both studies, from enhanced reaction to clinohumite in this study due to the presence of excess brucite in the starting material, or from different concentrations of defects in the two samples. The brackets on the reaction were combined with other measured and estimated thermodynamic data for clinohumite to determine its enthalpy of formation and entropy, in a revised version of the thermodynamic dataset of Holland and Powell (1998). The values obtained were ΔHf=-9607.29±3.05 kJ mol-1, S=445 J mol-1 K-1. These data were used to calculate positions of other reactions involving clinohumite. The calculations suggest a larger stability field for clinohumite than implied by the results of previous experimental studies, indicating a need for more high-pressure phase-equilibrium studies to provide better thermodynamic data.